2022
DOI: 10.1002/1878-0261.13335
|View full text |Cite
|
Sign up to set email alerts
|

mitoSomatic: a tool for accurate identification of mitochondrial DNA somatic mutations without paired controls

Abstract: Mitochondrial DNA (mtDNA) somatic mutations play important roles in the initiation and progression of cancer. Although next‐generation sequencing (NGS) of paired tumor and control samples has become a common practice to identify tumor‐specific mtDNA mutations, the unique nature of mtDNA and NGS‐associated sequencing bias could cause false‐positive/‐negative somatic mutation calling. Additionally, there are clinical scenarios where matched control tissues are unavailable for comparison. Therefore, a novel appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Our previous publications have provided somatic mtDNA mutation data from 110 patients with hepatocellular carcinoma (HCC) (private HCC cohort) and 432 patients with CRC (public CRC cohort). These datasets were compared to explore the mutational patterns of mtDNA among different types of cancer 22,33 . To further validate the findings of the private mtDNA mutation datasets, we acquired a public mtDNA mutation dataset from whole‐genome sequencing (WGS) of tumour tissues from 118 EOC, 344 HCC and 62 CRC patients.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous publications have provided somatic mtDNA mutation data from 110 patients with hepatocellular carcinoma (HCC) (private HCC cohort) and 432 patients with CRC (public CRC cohort). These datasets were compared to explore the mutational patterns of mtDNA among different types of cancer 22,33 . To further validate the findings of the private mtDNA mutation datasets, we acquired a public mtDNA mutation dataset from whole‐genome sequencing (WGS) of tumour tissues from 118 EOC, 344 HCC and 62 CRC patients.…”
Section: Methodsmentioning
confidence: 99%
“…These datasets were compared to explore the mutational patterns of mtDNA among different types of cancer. 22 , 33 To further validate the findings of the private mtDNA mutation datasets, we acquired a public mtDNA mutation dataset from whole‐genome sequencing (WGS) of tumour tissues from 118 EOC, 344 HCC and 62 CRC patients. The public dataset was obtained from the TCMA database ( http://bioinformatics.mdanderson.org/main/TCMA:Overview ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we have developed a package to identify tumorspecific mtDNA mutations in mtDNA NGS data, applicable to both tumor and nontumor tissues without paired controls 24 . Moreover, we have found that the copy number of mtDNA in the plasma of patients with HCC is significantly lower than that in tissue, and the cf-mtDNA fragments are shorter than those of cf-nDNA.…”
Section: Clinical Prognosis Indicationmentioning
confidence: 99%